Harmoni Islam dan Budaya Jawa dalam Tafsir Kitab Suci Al-Qur’an Basa Jawi - S. Supriyanto (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
This study aims to describe the harmonic modes between Islam dan Javanese culture in Javanese qur’anic commentary. The object material is Tafsir Al-Qur’an Suci Basa Jawi which studied using Gadamer’s hermeneutics. This is the book of tafsir which written based on the idea of Tafsir Anom V. The tafsir then was written, compiled, and publishd by KH. Raden Muhammad Adnan (1889-1969) and his descendants who lived in Keraton Surakarta.  The study shows that Tafsir Al-Qur’an Suci Basa Jawi is one of local qur’anic commentaries which strengthen harmonic modes between Islam and Javanese culture. There are three points of Javanese culture in harmony with Islam: the use of respectful language in Javanese, a harmony of Javanese Islamic mysticism and Javanese Islam as a way of wisdom. This is a local qur’anic commentary that harmonize the Javanese local culture with Islam.